Fenomena Judi Online Terhadap Kecenderungan Pemahaman Hadis di Era Disrupsi Digital - Hasanah, Uswatun; Isroyo, Citra Pertiwi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the understanding of hadith on the phenomenon of online gambling in the era of digital disruption. The method used in this study is qualitative with a descriptive approach and also library research or a form of data collection through literature. The results and discussion of this study show that online gambling is not allowed. Islam makes gambling a serious mistake and despises what a form of gambling is. As for this criminal gambling included in the jarimah ta'zir, everyone commits forbidden deeds and has no had, qisas, and kafarat, for the judge is given the freedom to punish with ta'zir based on his ijtihad which in case can prevent him from repeating his deeds of being beaten or imprisoned and given minor contempt. As for the provisions of the jarimah ta'zir which remain non-existent, all are left to the government or the courts, in which case it is the judge who determines, as for the intent of this determination.